Cutting-edge heat transfer: How hexagonal boron nitride nanofluids boost solar photovoltaic thermal (PVT) system performance? - Nurhanis Sofiah, Abd Ghafar; Samykano, Mahendran; Rajamony, Reji Kumar; Pasupuleti, Jagadeesh; Pandey, Adarsh Kumar; Nur Fatin, Sulaiman
This study evaluates the potential of hexagonal boron nitride (hBN) dispersed in distilled water to enhance the performance of indoor solar photovoltaic thermal (PVT) systems, with specific objectives to improve electrical efficiency, thermal efficiency, and exergy performance, while reducing entropy generation. The novelty of this work lies in the experimental application of hBN-water nanofluids in PVT systems, a topic not previously explored in existing literature, with the target to increase the efficiency of solar energy systems. The 0.5 % volume concentration of hBN-water nanofluids improved thermal conductivity and was integrated into the PVT system, evaluated at irradiances of 380, 580, and 780 W/m2 with a mass flow rate of 0.9 L/m. The nanofluid system demonstrated excellent dispersion stability, with zeta potential values exceeding ±30 mV. Experimental results showed that the nanofluid integrated PVT system reduced panel temperatures significantly, from 63 °C to 39 °C at 380 W/m2, leading to increased electrical power output from 12.03 W to 21.17 W. Electrical efficiency decreased with higher solar radiation, while thermal efficiency increased, with heat gain reaching 255 W at 780 W/m2, compared to 225 W for water cooling. Exergy efficiency was enhanced, reaching 8.7 % for the nanofluid system, compared to 5.8 % for water cooling and 5.3 % for no cooling. Exergy loss was reduced by approximately 2.9 % at 380 W/m2 and entropy generation showed a reduction of 2.8 %, highlighting the superior energy conversion efficiency of the nanofluid system. These findings demonstrate the potential of hBN-water nanofluids to improve the performance and sustainability of PVT systems.